Increasing Learning Achievement Through the Application of Inquiry Methods in Entrepreneurship Courses - Saut Maruli Tua Pandiangan; Fachrurazi Fachrurazi; Kevin Indajang; Yulia Novita; Donny Dharmawan (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to analyze increasing learning achievement through the application of inquiry method in entrepreneurship courses. The type of research used is classroom action. The subjects of this research were 30 students in Private University Medan City who were taken randomly. Data collection techniques use observation and documentation. Data analysis in this research uses descriptive quantitative method. The results of the research show that the application of the modified free inquiry method to the material of fostering an entrepreneurial spirit and creativity capital in entrepreneurship can improve learning achievement in Private University students in Medan City. Keywords: Learning Achievement, Inquiry Method, Entrepreneurship